ZnO/Graphene Composite from Solvent-Exfoliated Few-Layer Graphene Nanosheets for Photocatalytic Dye Degradation under Sunlight Irradiation - Vasanthi Venkidusamy; Sivanantham Nallusamy; Gopalakrishnan Nammalvar; Ramakrishnan Veerabahu; Arun Thirumurugan; Chidhambaram Natarajan; Shanmuga Sundar Dhanabalan; Durga Prasad Pabba; Carolina Venegas Abarzúa; Sathish-Kumar Kamaraj (Micromachines, 2023)
ZnO/graphene nanocomposites were prepared using a facile approach. Graphene nanosheets were prepared by ultrasonication-based liquid phase exfoliation of graphite powder in a low boiling point organic solvent, 1,2-Dichloroethane, for the preparation of ZnO/graphene nanocomposites. Structural properties of the synthesized ZnO/graphene nanocomposites were studied through powder XRD and micro-Raman analysis. The characteristic Raman active modes of ZnO and graphene present in the micro-Raman spectra ensured the formation of ZnO/graphene nanocomposite and it is inferred that the graphene sheets in the composites were few layers in nature. Increasing the concentration of graphene influenced the surface morphology of the ZnO nanoparticles and a flower shape ZnO was formed on the graphene nanosheets of the composite with high graphene concentration. The efficiencies of the samples for the photocatalytic degradation of Methylene Blue dye under sunlight irradiation were investigated and 97% degradation efficiency was observed. The stability of the nanocomposites was evaluated by performing five cycles, and 92% degradation efficiency was maintained. The observed results were compared with that of ZnO/graphene composite derived from other methods.